2018
DOI: 10.1101/285981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative cross-species analyses identify deficits in habituation learning as a widely affected mechanism in Autism

Abstract: 60Background: Although habituation is one of the most ancient and fundamental forms of learning, its 61 regulators and relevance for human disease are poorly understood. 62Methods: We manipulated the orthologs of 286 genes implicated in intellectual disability (ID) with or 63 without comorbid autism spectrum disorder (ASD) specifically in Drosophila neurons, and tested 64 these models in light-off jump habituation. We dissected neuronal substrates underlying the 65 identified habituation deficits and integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Failure to attenuate responses to repetition or to respond selectively to a change in auditory input could compromise language development Benasich & Tallal, 2002) and may also relate to broader aspects of cognitive inflexibility, which has been noted in several neurodevelopmental disorders including ASD, Prader-Willi, Rett Syndrome and Fragile X (American Psychiatric Association, 2013; Lewis & Kim, 2009;McDiarmid et al, 2019;Oakes et al, 2016). Further, failure in these basic learning mechanisms may indicate alterations in neural organisation, consistent with observations of atypical neural connectivity in developmental disorders as well as differences in the coordination of excitation and inhibition (Delbruck et al, 2019;Ethridge et al, 2016;Linke et al, 2018;Rubenstein & Merzenich, 2003).…”
supporting
confidence: 55%
“…Failure to attenuate responses to repetition or to respond selectively to a change in auditory input could compromise language development Benasich & Tallal, 2002) and may also relate to broader aspects of cognitive inflexibility, which has been noted in several neurodevelopmental disorders including ASD, Prader-Willi, Rett Syndrome and Fragile X (American Psychiatric Association, 2013; Lewis & Kim, 2009;McDiarmid et al, 2019;Oakes et al, 2016). Further, failure in these basic learning mechanisms may indicate alterations in neural organisation, consistent with observations of atypical neural connectivity in developmental disorders as well as differences in the coordination of excitation and inhibition (Delbruck et al, 2019;Ethridge et al, 2016;Linke et al, 2018;Rubenstein & Merzenich, 2003).…”
supporting
confidence: 55%
“…These defects might contribute to symptoms associated with defective cortical filtering, such as sensory hypersensitivity and other ASD features [98, 99]. In recent years, studies in Drosophila but also in other organisms have reported habituation deficits as a widely affected mechanism in models of ID/ASD disorders [100, 101]. Whether habituation deficits contribute to cognitive and learning defects observed in FOXP patients remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of habituation have been described in Drosophila , and a variety of assays are available for their assessment (Asztalos et al, 2007; Das et al, 2011; Kuntz et al, 2012; Paranjpe et al, 2012). Recently, Drosophila knockdown models of ∼300 ID genes were investigated in the light-off jump habituation paradigm (Box 1), revealing habituation deficits in more than 100 models (Fenckova et al, 2018). Interestingly, among the habituation-defective ID models, those with comorbid ASD were particularly enriched, suggesting that habituation could be a widely applicable readout for Drosophila studies of both disorders.…”
Section: Using Drosophila To Overcome Bottlenecks In Id and Asd Reseamentioning
confidence: 99%